FNB : developing a culture of innovation - Gaylard, Alison; Viedge, Conrad ([London] : SAGE, 2016)
First National Bank (FNB) has become known in the industry as a leader in banking innovation. When CEO Michael Jordaan took over the reins in 2004, he took innovation to a new level through the Innovators campaign. But now, in 2010, he was wondering how to sustain the energy the campaign had engendered in his staff. What more could he do to nurture the spirit of innovation that permeated the organisation?
Originally Published in: Gaylard, A., & Viedge, C. (2011). FNB: Developing a Culture of Innovation. WBS- 2011-2. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; First National Bank (South Africa); Creative ability in business -- Case studies; Banks and banking -- Case studies